Places and Preferences: A Longitudinal Analysis of Self-Selection and Contextual Effects. Issue 3 (21st October 2014) - Gallego, Aina; Buscha, Franz; Sturgis, Patrick; Oberski, Daniel
Abstract : Contextual theories of political behaviour assert that the contexts in which people live influence their political beliefs and vote choices. Most studies, however, fail to distinguish contextual influence from self-selection of individuals into areas. This article advances understanding of this controversy by tracking the left–right position and party identification of thousands of individuals over an eighteen-year period in England before and after residential moves across areas with different political orientations. There is evidence of both non-random selection into areas and assimilation of new entrants to the majority political orientation. These effects are contingent on the type of area an individual moves into and contextual effects are weak and dominated by the larger effect of self-selection into areas.